2018
DOI: 10.5194/amt-11-3801-2018
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine wake measurements with automatically adjusting scanning trajectories in a multi-Doppler lidar setup

Abstract: Abstract. In the context of the Perdigão 2017 experiment, the German Aerospace Center (DLR) deployed three long-range scanning Doppler lidars with the dedicated purpose of investigating the wake of a single wind turbine at the experimental site. A novel method was tested for the first time to investigate wake properties with ground-based lidars over a wide range of wind directions. For this method, the three lidars, which were space- and time-synchronized using the WindScanner software, were programmed to meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Goger et al (2018) found that in the COSMO model, turbulence kinetic energy (TKE) is systematically underestimated with a one-dimensional turbulence parameterization. Recent sensitivity studies by Yang et al (2017) showed that the parameters associated with turbulent mixing in an ABL parametrization have a large impact on 80 m wind speeds in the Weather Research and Forecasting model (WRF). They find that parameters associated with turbulence dissipation rate are responsible for approx-imately 50 % of the variance in 80 m wind speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Goger et al (2018) found that in the COSMO model, turbulence kinetic energy (TKE) is systematically underestimated with a one-dimensional turbulence parameterization. Recent sensitivity studies by Yang et al (2017) showed that the parameters associated with turbulent mixing in an ABL parametrization have a large impact on 80 m wind speeds in the Weather Research and Forecasting model (WRF). They find that parameters associated with turbulence dissipation rate are responsible for approx-imately 50 % of the variance in 80 m wind speeds.…”
Section: Introductionmentioning
confidence: 99%
“…In the study on instantaneous wind estimates [194], the turbulent quantities measured by three LiDARs staring at a point close to a sonic anemometer compared well with corresponding sonic anemometer measurements. In synchronized trinal LiDAR configurations, 3D wind velocity variance can be directly obtained by solving 3D linear equations [195,196].…”
Section: Retrieval Methods Of Multiple Lidarsmentioning
confidence: 99%
“…In a major shift from previous field studies, the mean and turbulent velocity fields were measured by six triumvirates of scanning Doppler lidars between a 25-and 75-m resolution over ~ 2−5-km hemispherical volumes. The scanning lidar datasets have already yielded insights into turbine wake behavior in complex terrain (Menke et al 2018;Wildmann et al 2018) as well as atmospheric recirculations in complex terrain (Menke et al 2019). Perdigão publications will be collected at https://www.atmos-chemphys.net/special_issue636_946.html.…”
Section: New European Wind Atlas and Perdigãomentioning
confidence: 99%